Investigation of Abundance and Diversity of Cantharidin Compounds in the Hycleus colligatus, Mylabris schrenki, Mylabris cincta, and Hycleus schah Species from Kerman Province, Iran - Sara sadat Nezhad-ghaderi; Arastoo Badoei-dalfard; Jamasb Nozari (Journal of Genetic Resources)
Cantharidin and cantharidin-related compounds (CRCs) are synthesized by Meloidae to defend against predators. Also, Cantharidin and CRCs are known as biopesticides. Because biopesticides are increasingly used to replace chemical pesticides in pest control, it is necessary to investigate the amount of cantharidin and CRCs (palasonin and palasoninimide) as known biopesticides. In this research, cantharidin content was determined in four species of Meloidae (Hycleus colligatus, Mylabris schrenki, Mylabris cincta, and Hycleus schah) which were abundant in Kerman province. Each species was divided into three groups including males, mated females, and virgin females. The results showed that Hycleus colligatus had the highest level of cantharidin (Mean± SE: 20.38± 0.49 µg/mg). The levels of cantharidin for Mylabris schrenki, Mylabris cincta, Hycleus schah were 12.44± 0.17, 5.24± 0.06, and 3.49± 0.03µg/mg, respectively. The level of cantharidin in mated females and virgin females in all species, had the highest and lowest levels, respectively. The results showed that only males can synthesize cantharidin and transfer it to females during mating. Mated females get this toxin from males during mating and use it for defending eggs from attacking predators and inducing feeding versions in predators exposed to the toxin. Also, in this research, palasonin and palasoninimide content were determined in these four species. Palasonin and palasoninimide were found in mated females but not in males indicating that CRCs do not have the same transfer pattern as cantharidin and thus unlike cantharidin, could not have been transferred from males to females. The study showed that in mated females of four species, the percentage of cantharidin was more than palasonin and palasoninimide.